Four Escherichia coli O157:H7 phages: a new bacteriophage genus and taxonomic classification of T1-like phages. - Yan D Niu; Tim A McAllister; John H E Nash; Andrew M Kropinski; Kim Stanford (PLoS ONE, 2014)
The T1-like bacteriophages vB_EcoS_AHP24, AHS24, AHP42 and AKS96 of the family Siphoviridae were shown to lyse common phage types of Shiga toxin-producing Escherichia coli O157:H7 (STEC O157:H7), but not non-O157 E. coli. All contained circularly permuted genomes of 45.7-46.8 kb (43.8-44 mol% G+C) encoding 74-81 open reading frames and 1 arginyl-tRNA. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis revealed that the structural proteins were identical among the four phages. Further proteomic analysis identified seven structural proteins responsible for tail fiber, tail tape measure protein, major capsid, portal protein as well as major and minor tail proteins. Bioinformatic analyses on the proteins revealed that genomes of AHP24, AHS24, AHP42 and AKS96 did not encode for bacterial virulence factors, integration-related proteins or antibiotic resistance determinants. All four phages were highly lytic to STEC O157:H7 with considerable potential as biocontrol agents. Comparative genomic, proteomic and phylogenetic analysis suggested that the four phages along with 17 T1-like phage genomes from database of National Center for Biotechnology Information (NCBI) can be assigned into a proposed subfamily "Tunavirinae" with further classification into five genera, namely "Tlslikevirus" (TLS, FSL SP-126), "Kp36likevirus" (KP36, F20), Tunalikevirus (T1, ADB-2 and Shf1), "Rtplikevirus" (RTP, vB_EcoS_ACG-M12) and "Jk06likevirus" (JK06, vB_EcoS_Rogue1, AHP24, AHS24, AHP42, AKS96, phiJLA23, phiKP26, phiEB49). The fact that the viruses related to JK06 have been isolated independently in Israel (JK06) (GenBank Assession #, NC_007291), Canada (vB_EcoS_Rogue1, AHP24, AHS24, AHP42, AKS96) and Mexico (phiKP26, phiJLA23) (between 2005 and 2011) indicates that these similar phages are widely distributed, and that horizontal gene transfer does not always prevent the characterization of bacteriophage evolution. With this new scheme, any new discovered phages with same type can be more properly identified. Genomic- and proteomic-based taxonomic classification of phages would facilitate better understanding phages diversity and genetic traits involved in phage evolution.